The Effect of Product Quality, Price and Promotion on Purchasing Decisions - Asep Saepuloh; Doris Roif Hisani (INNOVATION RESEARCH JOURNAL, 2020)
Currently in the mobile phone business going on a very tight competition, any company or operator ofa mobile card issuing competing to create various alternatif option to influence purchasing decisionsand win the competition. This study aims to test the effect of product quality, price, and promotion onpurchasing decisions. The number of samples in this study were 100 Gresik Telkomsel consumers.Analysis of the data used is multiple linear regression analysis. The results of this study concluded thatthe results of simultaneous testing of product quality, price, and promotion of purchasing decisions.The results of partial testing of product quality have a significant effect on purchasing decisions, priceshave a significant effect on purchasing decisions, and promotions have a significant effect onpurchasing decisions.